Jarak Tempuh dan Disiplin Kerja: Benarkah Karyawan yang Tinggal Dekat Lebih Disiplin? - agung kristanto, Yunus; Septiawan, Fajar Eryanto Septiawan; Kristanto, Yunus Agung (Jurnal Bisnis dan Kewirausahaan, 2025)
Work discipline is a key factor in increasing employee productivity and efficiency, especially in the context of global competition. This study aims to explore the relationship between the distance from home to the workplace and the level of work discipline of employees in Yogyakarta. The method used is an independent sample t-test to compare the level of discipline between employees who live close and far from the workplace. The results of the study show that employees who live closer have a higher level of discipline, with a significant difference indicated by a p-value < 0.05. The conclusion of this study confirms the importance of considering travel distance in human resource management policies, as well as the need for companies to address the negative impacts of long travel distances on employee discipline. These findings are expected to contribute to better management literature and business practices.